FOSTERING STUDENTS SCIENTIFIC REASONING THROUGH 5E MODEL OF INSTRUCTION ON TENTH GRADE STUDENT OF PHYSICS CLASS IN SMAN 15 SURABAYA - Noly Shofiyah; Z. A. Imam Supardi; Budi Jatmiko (Universitas Negeri Surabaya, 2017)
The aim of this study was to develop instructional package using 5E model of instruction to foster students scientific reasoning. The instructional package consisting of lesson plan, handout, students worksheet, and scientific reasoning test was developed by using the four-D model. Subject of research in this study was instructional package using 5E model of instruction which was tried out on tenth grade students of SMAN 15 Surabaya. The tryout was conducted by using the one-group pre-test post- test design. This study used three techniques for collecting data, namely observation, test, and questionnaire. The obtained data were processed with descriptive qualitative analysis. The findings revealed that the developed instructional package reflecting th e 5E model was valid to be implemented in classroom, the completion of the lesson plan was categorized excellent, and students were engaged actively in the instruction of the 5E model as shown by their dominant activities namely performing experiment and discussion. The other findings showed that the 5E model of instruction is effective to foster students scientific reasoning skills and students gave positive responses to the implementation of the developed instructional package. However, there were obstacles that teacher and students faced during instructional process. Regarding to the findings, then it can be concluded that the developed instructional package reflecting 5E model of instruction is effective to be implemented to foster students scientific reasoning.